Regime der Anerkennung Kämpfe um Wahrheit und Recht in der Aufarbeitung der argentinischen Militärdiktatur - Hasgall, Alexander (Histoire, 2016)
What meaning does recognition have in the context of the rehabilitation of tyranny? This volume provides answers.